Developing a Rural-Based English Curriculum: Lessons from an International Baccalaureate Program - Aip Syaepul Uyun; Rahma Sakina; Fitriani Nurhalimah (Universitas Islam Negeri Palopo, 2026)
The quality of English education in rural Indonesia remains significantly low. Limited teacher competence, inadequate resources, and minimal exposure to authentic language use are the major issues revealed. Building on a previous needs analysis conducted in rural schools, this study represents the second phase of a larger Research and Development (R&D) project aimed at developing a contextual and feasible English curriculum for rural settings. Using a case study design, the research examines the implementation of a combined national and International Baccalaureate (IB) curriculum at a rural school in northern Bandung. Data were collected through interviews, classroom observations, and document analysis. The findings reveal that the school employs an institutional curriculum integrating national standards with IB principles particularly multiculturalism, communicative competence, and contextual learning supported by Cummins’ four-dimension framework: activating background knowledge, scaffolding, extending language, and affirming identity. The analysis further demonstrates that rural learners require curriculum models emphasizing Basic Interpersonal Communication Skills (BICS), student-centered methods, and adaptable low-cost resources. Insights gained from the exemplary IB-implemented rural school provide a benchmark for translating needs-analysis findings into practical curriculum design. This study contributes a model for English curriculum development tailored to rural Indonesian schools by aligning global frameworks with local needs.